Bridging the gap among social classes in Chimamanda Ngozi Adichie’s Half of a Yellow Sun (2006) - Abdou Sene (Center for Humanities and Innovation Studies, 2021)
The Biafra War has been the subject of many historical accounts and literary texts. Among the novels produced about the Biafra War is Chimamanda Ngozi Adichie’s Half of a Yellow Sun (2006) where the author recounts not only the events leading to the war but also those during and just after the conflict. Though the events of the Biafra War constitute the central theme in Half of a Yellow Sun, Adichie also deals with the relationships among social classes in this novel. One may wonder why the author shows that some upperclass people are keen on their difference, their ‘superiority’, and, on the other hand, people of the upper and middle classes are human and respectful towards lower-class persons. What is the purpose of the writer in drawing this parallel? From a socialist and humanist perspective, this article deals with “bridging the gap among social classes in Chimamanda Ngozi Adichie’s Half of a Yellow Sun.” Based on sociology, psychology, socialism, and humanism, the paper will first deal with the criticism of the Nigerian upper class and then with Adichie’s advocacy for a socialist and humanist society.